The relationship between serum vitamin D level and asthma severity in asthmatic children (aged 1-15 years) in Ardabil, 2012-13 - Ahmadabadi, Farzad; Mirzarahimi, Mehrdad; Barak, Manouchehr; Ahadi, Adel; Alipour, Rasoul (International Journal of Research in Medical Sciences, 2017)
Background:Vitamin D plays an important role in many immune and allergic diseases, and its deficiency is more in areas with low solar radiation. Asthma is a common disease in children of Ardabil city. The present study was designed to evaluate vitamin D levels in asthmatic children in Ardabil. Methods:A total of 100 asthmatic children (40% boys and 60% girls) with a mean age of 5.7 ± 3.46 years (1-15 years) and who visited the Bou-Ali pediatric hospital were included. Vitamin D levels, disease course, IgE levels, and eosinophil counts were evaluated. A group of healthy children was also included to compare vitamin D levels between asthmatic and non-asthmatic children. All data were analyzed by statistical methods in SPSS v.16. Results: The vitamin D levels in asthmatic children were lower than those in the healthy group. Furthermore, the increase in the vitamin D level was significantly associated with lower history of hospitalization (P = 0.02), better response to bronchodilator treatment (P = 0.01), lower IgE level (P = 0.02), and decrease in the mean age of children (P = 0.04). However, no significant association between vitamin D levels and sex (P = 0.08), history of anti-inflammatory drug use (P = 0.78), and eosinophil count (P = 0.08) was observed in asthmatic children. Conclusion:Results showed that vitamin D deficiency was more common in asthmatic than in non-asthmatic children and the level of vitamin D was directly associated with the response of the children to treatment.